Correlates of Academic Performance in Online Higher Education: A Systematic Review - Chung, Jennifer; McKenzie, Stephen; Schweinsberg, Ashleigh; Mundy, Matthew Edward (Frontiers in Education, 2022)
The existing steady and continual rise of online learning in higher education has been accelerated by COVID-19 and resulted in a move away from solely on-campus teaching. Prior to the pandemic, online education was providing higher education to students who were returning to study to up-skill, are employed full-time, caring for family members, living rurally or remotely and/or for whom otherwise face-to-face campus learning was not a preference or option. To understand how we can better support online students in their unique circumstances and create an optimal learning environment, we must understand the factors associated with academic achievement within an online setting. This systematic review involved a search of relevant databases published between January 2009 and May 2021 examining factors and constructs related to academic performance in online higher education settings. Across 34 papers, 23 (67.6%) explored factors and constructs related to student characteristics including cognitive and psychological, demographic, university enrolment, and prior academic performance. Twenty-one (61.8%) papers explored learning environment factors including engagement, student experience, course design, and instructor. Our overall synthesis of findings indicates that academic performance in online learning is most strongly associated with motivation (including self-efficacy), and self-regulation. We propose three main implications of our review for online learning stakeholders such as educators and designers. Firstly, we argue that the wellbeing of online learners is important to understand, and future research should explore its impact on students’ experience and success in online higher education. Secondly, we emphasise the importance of developing and designing online courses utilising relevant frameworks and evidence-based principles. Finally, we propose an approach to promoting improved student cognitive and psychosocial experiences (such as self-efficacy, self-regulation, and perceived support) could be achieved by creating and incorporating an online learning orientation module at the commencement of enrolment. Systematic Review Registration: (website), identifier (registration number).